Digital Information and Communication Technologies for teaching and learning Natural Sciences and Mathematics from the BNCC perspective (Research, Society and Development, 2021)
This research aims to analyze the role of Digital Information and Communication Technologies (DICT) for the teaching and learning process of Natural Sciences and Mathematics and its Technologies, presented at Common National Curricular Base (BNCC). To achieve the proposed objective, this study adopts a qualitative methodological approach, of documentary type, as to its outline, in which an analysis of the BNCC - High School stage was carried out. As a result, this work brings an analysis and discussion about the competences and skills to be developed from the use of digital technologies for the areas of Natural Sciences and Mathematics and their Technologies. We found that the area of Natural Sciences has three specific competences and 26 skills, with DICT being addressed in one competency with 10 related skills, while the Mathematics area has five specific competences and 43 skills of which four competences and 19 skills suggest the use of DICT. With these results, it can be concluded that DICT are important for the teaching and learning process, as they support the development of competences and skills in the areas of Natural Sciences and Mathematics and their Technologies.